(untitled) (Conference on English Language Teaching, 2025)
The creation of artificial intelligence (AI) has made it possible to build many helpful and interesting tools. These tools are designed to make studying easier, more fun, and more effective for people all over the world. This research aims to compare two AI systems, ChatGPT and DeepSeek, to evaluate which produces clearer, more logical, and reliable responses. The study analyzes these ratings and comments to determine how users judge the "sense-making" and accuracy of each AI. By relying on user perspectives, this work offers practical insights for improving AI tools and helping people choose the right system for tasks requiring logical, context-aware responses. This study used a qualitative descriptive method. The data of this research were collected through survey and questionnaire to university students. The survey was conducted via Instagram polling to find respondents who had interacted with ChatGPT and DeepSeek. The questionnaire was delivered to get information about the accuracy of ChatGPT and DeepSeek.